Pengaruh Warna Lampu yang Berbeda terhadap Laju Pertumbuhan Chaetoceros calcitrans - Rahmatullah, Rijal; Nuarsa, I Wayan; Surya Indrawan, Gede (Journal of Marine Research and Technology; Vol 7 No 1 (2024): FEBRUARI 2024DO - 10.24843/JMRT.2024.v07.i01.p08, 2024)
Chaetoceros calcitrans is one of the diatoms commonly used as a natural feed for cultivated fish larvae. The cultivation of C. calcitrans as natural feed is influenced by various factors, including light as a source for photosynthesis. This research aimed to determine the effect of different light colors on the growth rate and identify the optimal color for the growth rate of C. calcitrans . The research was conducted at the BPIU2K Karangasem laboratory. The experimental method with a Completely Randomized Design (CRD) was employed, consisting of three treatments and one control. Treatment A used yellow-colored lights, treatment B used blue-colored lights, treatment C used green-colored lights, and treatment D served as the control using white-colored lights. The observed parameters included population density, specific growth rate, and doubling time . The results were analyzed using ANOVA. The findings indicated that the light color significantly affected the population density, specific growth rate, and doubling time with a value of (Sig.<0.05). The best treatment was the use of white-colored lights, followed by yellow-colored lights, which resulted in the highest density on the 5 th day, reaching 1.238,88 x 10 4 cells/ml and 1.040,55 x 10 4 cells/ml, respectively. The specific growth rate for white and yellow lights was 8.51%/hour and 7.53%/hour, respectively. The doubling time for white and yellow lights was 14.93 hours and 15.75 hours, respectively. White and yellow light irradiation exhibited wavelengths suitable for the cultivation of C. calcitrans .